2020
DOI: 10.1016/j.omtn.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related lncRNA to Construct Novel Signature and Predict the Immune Landscape of Human Hepatocellular Carcinoma

Abstract: The signature composed of immune-related long noncoding ribonucleic acids (irlncRNAs) with no requirement of specific expression level seems to be valuable in predicting the survival of patients with hepatocellular carcinoma (HCC). Here, we retrieved raw transcriptome data from The Cancer Genome Atlas (TCGA), identified irlncRNAs by co-expression analysis, and recognized differently expressed irlncRNA (DEirlncRNA) pairs using univariate analysis. In addition, we modified Lasso penalized regression. Then, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
200
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(206 citation statements)
references
References 60 publications
(57 reference statements)
2
200
1
Order By: Relevance
“…P < 0.05, delta Beta value ≥ 0.2. A list of identified immune-related genes was downloaded from the ImmPort database ( http://www.immport.org ) [ 22 ] and was used to screen IR-DEGs using a coexpression strategy. The extent of immune cell infiltration was obtained from the Tumor IMmune Estimation Resource (TIMER), which estimates the immune cell infiltrates in patients from the TCGA database ( https://cistrome.shinyapps.io/timer/ ).…”
Section: Methodsmentioning
confidence: 99%
“…P < 0.05, delta Beta value ≥ 0.2. A list of identified immune-related genes was downloaded from the ImmPort database ( http://www.immport.org ) [ 22 ] and was used to screen IR-DEGs using a coexpression strategy. The extent of immune cell infiltration was obtained from the Tumor IMmune Estimation Resource (TIMER), which estimates the immune cell infiltrates in patients from the TCGA database ( https://cistrome.shinyapps.io/timer/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al showed that lncRNA 01094 induces radioresistance via regulation of the miR-577/CHEK2/ FOXM1 axis (13). Recently, the results of several studies have shown that lncRNAs also have a significant impact on the immune system in cancers such as triple-negative breast cancer, hepatocellular carcinoma (HCC), and glioblastoma multiforme (14)(15)(16), and these lncRNAs have been termed immune-related lncRNAs (irlncRNAs). Liu et al's study revealed that LINC00973 acts as an immune suppressor in ccRCC via its positive regulation of Siglec-15 (17).…”
Section: Introductionmentioning
confidence: 99%
“…As lncRNAs are correlated with ir-genes, these lncRNAs may be involved in regulating the tumor immune microenvironment or the immune cells. The models of IRlncRs were applied to predict the prognosis of breast cancer, 30 hepatocellular carcinoma, 31 clear cell renal cell carcinoma, 20 and pancreatic cancer, 32 except for melanoma. In this study, we first established a novel model with lncRNAs signature to predict melanoma prognosis.…”
Section: Discussionmentioning
confidence: 99%